2008
DOI: 10.1089/tea.2007.0153
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion, Proliferation, and Osteogenic Differentiation of a Mouse Mesenchymal Stem Cell Line (BMC9) Seeded on Novel Melt-Based Chitosan/Polyester 3D Porous Scaffolds

Abstract: The aim of the present work was to study the biological behavior of a mouse mesenchymal stem cell line when seeded and cultured under osteogenic conditions onto novel processed melt-based chitosan scaffolds. Scaffolds were produced by compression molding, followed by salt leaching. Scanning electron microscopy (SEM) observations and lCT analysis showed the pore sizes ranging between 250 and 500 lm and the interconnectivity of the porous structure. The chitosan-poly(butylenes succinate) scaffolds presented high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 40 publications
1
25
0
3
Order By: Relevance
“…SEM micrographs of the porous scaffolds are presented in Figure 2; Figure 2a shows the morphology of scaffolds 4 mm in diameter and 1 mm thick. Previous studies (Alves da Silva et al , 2010; Costa‐Pinto et al , 2008; Oliveira et al , 2008) demonstrated that these scaffolds had adequate porosity (Figure 2b) to allow extensive cell proliferation.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…SEM micrographs of the porous scaffolds are presented in Figure 2; Figure 2a shows the morphology of scaffolds 4 mm in diameter and 1 mm thick. Previous studies (Alves da Silva et al , 2010; Costa‐Pinto et al , 2008; Oliveira et al , 2008) demonstrated that these scaffolds had adequate porosity (Figure 2b) to allow extensive cell proliferation.…”
Section: Resultsmentioning
confidence: 85%
“…For that, we tested several blends with a mouse mesenchymal stem cell line (BMC9), promoting differentiation into the osteogenic lineage. The results evidenced that the chitosan–PBS blend formulation, 50% wt and 60% porosity, showed the best performance in terms of cell behaviour (Costa‐Pinto et al , 2008). Further studies were performed using human bone marrow mesenchymal stem cells (hBMSCs) in fibre‐mesh scaffold morphology, with excellent results in terms of cell adhesion, proliferation and osteogenic differentiation (Costa‐Pinto et al , 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies have reported the use of CS scaffolds (Costa‐Pinto et al , 2008; Heinemann et al , 2008; Seol et al , 2004), the main disadvantage of these scaffolds is the fabrication of the scaffold according to the size of the defect, or carving the graft to fit the defect. This could result in additional bone loss and trauma.…”
Section: Discussionmentioning
confidence: 99%
“…To prove the concept of in situ pore formation in vitro , previous studies simulating the inflammatory response were performed, and the formation of pores was clearly visible when lysozyme was incorporated in CaP chitosan scaffolds 2. The combination of chitosan with other biodegradable materials has already been shown to be effective for bone‐related applications 11–13. The inclusion of starch in chitosan matrices constitutes an interesting approach towards obtaining scaffolds with enhanced degradation rates since starch is acting as a sacrifice material 1.…”
Section: Introductionmentioning
confidence: 99%